Study of an evaluation method of earthquake-proof capacity of a community during an earthquake - Ren, Tianxiang; Wang, Zhihui; Ma, Yan; Yan, Jinkai; Liu, Kai; Li, Hailong (Frontiers in Earth Science, 2024)
In dealing with the occurrence of earthquakes, urban communities and the people within the system should primarily consider the geological background, secondary hazards caused by earthquakes, countermeasures to mitigate earthquake disasters, community connectivity, and the impact of various indicators and criteria on the earthquake-proof capacity of the community. It is important to comprehensively assess these factors to ensure the community is well-prepared to withstand an earthquake. In this paper, taking a place in Shenzhen (China) as an example, the proposed evaluation method of earthquake-proof capacity during occurrence of an earthquake is preliminarily tested, and the results reflect the comprehensive capacity of communities. The assessment is an evaluation method framework that focuses more on improve disaster response capacity and resilience of urban communities effectively.